3(6-k)=-3

Simple and best practice solution for 3(6-k)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6-k)=-3 equation:


k in (-oo:+oo)

3*(6-k) = -3 // + 3

3*(6-k)+3 = 0

3*(6-k)+3 = 0

21-3*k = 0

21-3*k = 0

21-3*k = 0 // - 21

-3*k = -21 // : -3

k = -21/(-3)

k = 7

k = 7

See similar equations:

| 16+x+121=180 | | 4x+7y=72 | | 16+x+12=180 | | 6(3+2h)=3(3h-2) | | 4x^2-19x+30=4x+2 | | 6(-7+7a)=-420 | | 6(3a+6)=-126 | | 3(8+2d)=84 | | 4(-4x+1)=-156 | | 3(-1a-6)=-18 | | 3(-3+d)=21 | | 2l+2w=50 | | 6(-6x+10)=348 | | 2(-3k-2)=-58 | | 4(-2+2x)=64 | | 5(3+3a)=45 | | 4(6-3d)=-108 | | 5(7d-5)=80 | | 3(-3-d)=24 | | 6n+3=-3n+30 | | -k+6=42+3k | | 4w+9=2w+29 | | 9+4d=3d+12 | | 6+7a=3a-22 | | 6w+9=33+3w | | x^2+3x+4=8 | | 44/7+88=b | | -2-5x=x-44 | | 9+7x=x+15 | | d+7=40+4d | | 3d-9=0+6d | | 5a+6=-54-7a |

Equations solver categories